Perspectives on land use and plant cover in Pucallpa (Perú) between 2000 and 2023 - Indara Venecia Dávila del Valle; Renato Edu Barzola Gomez; Ciza Zarvia Rosario Ramon (ARQUISUR Revista, 2025)
This study aims at analyzing land use changes, plant cover loss, and urban expansion development in Ucayali region, Perú, by using tele-detection and geospatial analysis techniques applied to LANDSAT images from years 2000, 2005, 2015, and 2023. Eight types of land cover and use (CUS, by its initials in Spanish) are identified ‒excluding water bodies‒ according to satellite data analyzed using ARCMAP 10.4 software. Changes in land use and urban development are interpreted by means of supervised and unsupervised classification techniques, using the closest maximum likelihood algorithm and the Corine Land Cover system adjusted to Perú. Finally, a significant land-use transformation was evident, marked by a reduction in vegetation cover and an increase in areas dedicated to crops and pastures. Despite some reforestation efforts, soil degradation and biodiversity loss remain a concern. This highlights the need to implement effective environmental conservation strategies in the region and the importance of ongoing monitoring to sustainably manage natural resources in one of the most important regions of the Peruvian rainforest.